2004
DOI: 10.1186/1472-6874-4-s1-s11
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a reduced fertility rate on women's health

Abstract: Health Issue: Total fertility rates (TFRs) have decreased worldwide. The Canadian fertility rate has gone from 3.90 per woman in 1960 to 1.49 in 2000. However, not many studies have examined the impact on women's health of reduced fertility rates, delayed fertility and more births to unmarried women. This paper presents information on the relation between family size and specific determinants of health. Key Findings:The rate of TFR decline varies considerably by geographic location and sociodemographic subgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
8
1
Order By: Relevance
“…Although several studies in North America, Africa and South America (i.e., Chen et al, 2001;Ogilvie et al, 2007;Sowell et al, 2002;Myer et al, 2007;Oladapo et al, 2005;Nobrega et al, 2007) have investigated predictors of fertility intentions, these studies have not examined psychological variables, such as stigma and psychological distress, as either correlates or moderators of fertility intentions. 58.6% of the sample reported that they intended to have children, which is high compared to rates found in the general Canadian population (37.5%; Payne, 2006). The current study found that higher levels of social support, increased perceived stigma, African ethnicity and residing in Toronto were associated with increased fertility intentions.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Although several studies in North America, Africa and South America (i.e., Chen et al, 2001;Ogilvie et al, 2007;Sowell et al, 2002;Myer et al, 2007;Oladapo et al, 2005;Nobrega et al, 2007) have investigated predictors of fertility intentions, these studies have not examined psychological variables, such as stigma and psychological distress, as either correlates or moderators of fertility intentions. 58.6% of the sample reported that they intended to have children, which is high compared to rates found in the general Canadian population (37.5%; Payne, 2006). The current study found that higher levels of social support, increased perceived stigma, African ethnicity and residing in Toronto were associated with increased fertility intentions.…”
Section: Discussioncontrasting
confidence: 55%
“…Women were recruited from all HIV clinics and AIDS service organizations in British Columbia, and a total of 182 women of childbearing age were surveyed. 25.8% of the sample indicated they intended to have children (Ogilvie et al, 2007), while in the general Canadian population, approximately 3 7.5% of women indicated they intended to have children (Payne, 2006). In multivariable analyses, being younger, not being aboriginal and being in a stable relationship were associated with higher fertility intentions.…”
Section: Fertility Intentions and Desires In Hiv+ Womenmentioning
confidence: 92%
“…[ 1 ] The fertility rate directly influences maternal health, and eventually socioeconomic status of the people, family, society, and at large the economy of a nation. [ 2 3 4 ] Recent London Summit on Family Planning 2020 is a step to revamp the activities of population stabilization including TFR.…”
Section: Introductionmentioning
confidence: 99%
“…This rate is comparable to that of the general population (Ogilvie et al, 2007;Payne, 2003). The implication is that Canadian women appear to have similar reproductive intents regardless o f their HIV/AIDS serostatus (Ogilvie et al, 2007).…”
Section: Hiv/aids and Fertilitymentioning
confidence: 57%
“…Research shows that, in Canada and other developed countries, mother-to-child-transmission was reduced to 0.1% if the mothers adhered to HARRT for at least 4 weeks before delivery but for women with HIV, becoming a mother brings with it challenges beyond what HIV-negative mothers experience (Bitnun et al, 2014;Loutfy et al, 2009;Ogilvie et al, 2007). Research in Canada showed that, fertility desires and expectation to have children among women living with HIV are similar to HIV negative women (Loufty et al, 2009;Ogilvie et at., 2007;Payne, 2003).…”
Section: Background Of Studymentioning
confidence: 99%